2017
DOI: 10.24014/jp.v12i2.3230
|View full text |Cite
|
Sign up to set email alerts
|

Religiusitas Dengan Gaya Hidup Hedonisme: Sebuah Gambaran Pada Mahasiswa Universitas Syiah Kuala

Abstract: AbstrakGaya hidup hedonisme adalah pola hidup yang dinyatakan dalam aktivitas, minat, dan opini sebagai pencerminan dari keinginan untuk mencari kesenangan dalam hidupnya.Gaya hidup hedonis dapat menimbulkan dampak negatif salah satunya keinginan untuk terus berhura-hura. Penelitian ini bertujuan untuk mengetahui hubungan antara religiusitas dengan gaya hidup hedonisme pada mahasiswa S1 Universitas Syiah Kuala.. Sampel dalam penelitian ini adalah mahasiswa aktif S1 Unsyiah, berusia 18-22 tahun (masa remaja akh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
7
0
8
Order By: Relevance
“…This is supported by research that student age dominates hedonic behavior and according to the phenomena described in the previous chapter. [73] It can be concluded that the phenomenon that occurred in this study, tested on the students of Syarif Hidayatullah State Islamic University in Jakarta representing Muslim women wearing hijab in the modern era. The author realizes how important it is to limit yourself to avoid hedonic behavior whose orientation is only for pleasure in life.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…This is supported by research that student age dominates hedonic behavior and according to the phenomena described in the previous chapter. [73] It can be concluded that the phenomenon that occurred in this study, tested on the students of Syarif Hidayatullah State Islamic University in Jakarta representing Muslim women wearing hijab in the modern era. The author realizes how important it is to limit yourself to avoid hedonic behavior whose orientation is only for pleasure in life.…”
Section: Resultsmentioning
confidence: 89%
“…The phenomenon of hedonic lifestyle has been discussed in various universities in Indonesia. This is evidenced by research using case studies [10] ; [11]; [12] that hedonic behavior is found in students. The case study shows that the hedonic lifestyle considers the pleasures and pleasures of life as the main goals in one's life.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Psychological study demonstrates that religious beliefs and practices are associated with greater life satisfaction, happiness, positive affect and increased morale (Koenig and Larson, 2001). Studies also proved the negative relationship between religiosity and juvenile delinquency (Aviyah and Farid, 2014;Nisya and Sofiah, 2012); and a negative relationship between religiosity and the lifestyle of hedonism (Saputri and Rachmatan, 2017). Other findings indicate no relationship between religiosity and attitudes toward terror behavior in prisoners of terrorism cases in Indonesia (Pertiwi and Chrisharyanto, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Hedonistic lifestyle ini akan menjadi ciri khas dari mahasiswa yang akan membentuk identitas yang berbeda dengan identitas pada masa remaja Penelitian ini penting untuk diteliti yang pertama karena belum pernah ada penelitian yang dapat membuktikan pengaruh antara citra diri terhadap kecenderungan hedonistic lifestyle. Penelitian sebelumnya yang telah diketahui oleh peneliti yaitu terkait penggabungan hedonistic lifestyle dengan kontrol diri yang dilakukan penelitian oleh Azizah & Indrawati (2015), konsep diri yang dilakukan penelitian oleh Brilliandita & Putrianti (2015), persepsi yang dilakukan penelitian oleh Nadzir (2015), religiusitas yang dilakukan penelitian oleh Saputri & Risana (2016), Shoping Addiction yang dilakukan penelitian oleh Prasetyo (2017), konformitas teman sebaya yang dilakukan penelitian oleh Sholikhah & Dhania (2017), keluarga yang dilakukan penelitian oleh Trimartati (2014), regulasi emosi yang dilakukan penelitian oleh Anjelita (2017), Konsumtif yang dilakukan penelitian oleh Anggraini & Santhoso (2017), harga diri yang dilakukan penelitian oleh Maisyaroh (2016), dan kepribadian yang dilakukan penelitian oleh Amalia (2017).…”
unclassified